Algal symbiont genera but not coral host genotypes correlate to stony coral tissue loss disease susceptibility among Orbicella faveolata colonies in South Florida - Klein, Allison M.; Sturm, Alexis B.; Eckert, Ryan J.; Walker, Brian K.; Neely, Karen L.; Voss, Joshua D. (Frontiers in Marine Science, 2024)
Stony coral tissue loss disease (SCTLD) has spread throughout the entirety of Florida's Coral Reef (FCR) and across the Caribbean, impacting at least 30 coral species. The threatened hermatypic coral, Orbicella faveolata, demonstrates intraspecific variation in SCTLD affectedness with some colonies experiencing chronic disease lesions, while other nearby O. faveolata colonies appear unaffected with no disease signs over long monitoring periods. This study evaluated potential genotypic underpinnings of variable disease responses to SCTLD by monitoring and sampling 90 O. faveolata colonies from southeast Florida and the lower Florida Keys. High resolution analyses of >11,000 single nucleotide polymorphisms (SNPs) generated from 2bRAD sequencing indicated there were no SNP loci or genetic lineages significantly associated with O. faveolata SCTLD affectedness. Genotypic differences may still contribute to SCTLD susceptibility; however, these differences were not captured using this reduced representation sequencing approach. Algal symbiont community structure characterized from 2bRAD data revealed that the presence of Durusdinium spp. corresponded with SCTLD-affected colonies as compared to unaffected colonies, suggesting that algal symbiont community make-up may play some role in SCTLD resistance. Data generated by this study will be combined with Deleted: influence complementary molecular and physiological approaches to further investigate the complex drivers of intraspecific SCTLD susceptibility and resilience.underscoring the disease's remarkable capacity for rapid transmission (Sharp et al. 2020).Further south, SCTLD has also affected hundreds of kilometers of reef throughout the Florida Keys with severe losses in coral cover (Muller et al. 2020;Williams, Walter, and Muller 2021).Coral species vary in their susceptibility to SCTLD, and are categorized into three susceptibility groups: high, intermediate, and low (Meiling et al. 2020; Florida Coral Disease Response Research & Epidemiology Team 2018). Highly susceptible species such as Dendrogyra cylindrus, Dichocoenia stokesii, and Meandrina meandrites succumb very rapidly to the disease, with total colony mortality occurring within one week to two months of initial disease onset (Florida Coral Disease Response Research & Epidemiology Team 2018). Low-